Preparation method of series of M-TCBB metal organic framework materials and application of M-TCBB metal organic framework materials in adsorption of sulfur dioxide and ammonia gas
By preparing the series of M-TCBB metal organic frame materials, the stability and adsorption capacity of MOFs when adsorbing sulfur dioxide and ammonia is solved, and efficient and stable gas capture performance is achieved, especially in humid conditions, which shows excellent adsorption effect.
Patent Information
- Application Number
- CN202510169484.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-17
AI Technical Summary
When adsorbing sulfur dioxide and ammonia, existing MOFs materials have problems such as poor adsorption cycle stability, low adsorption capacity and water vapor competing for adsorption.
The series of M-TCBB metal organic frame materials were prepared by solvothermal method, and MOFs structures with high stability and high capture performance were constructed by selecting different metal types (such as yttrium, zirconium, hafnium, cerium, thorium) and [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid as organic ligands.
It is achieved that the adsorption stability and adsorption amount of MOFs to sulfur dioxide and ammonia are improved while keeping the topological structure unchanged, and water vapor-enhanced adsorption characteristics are shown under humid conditions.
Smart Images

Figure CN119842092A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorbent preparation, and specifically relates to a preparation method of a series of M-TCBB metal organic framework materials and application thereof in adsorbing sulfur dioxide and ammonia. Background Art
[0002] In industrial production processes, toxic industrial gases (TICs) such as sulfur dioxide (SO2), ammonia (NH3), hydrogen sulfide (H2S), nitrogen oxides (NOx) and carbon monoxide (CO) are widely used as chemical raw materials to produce various chemicals. However, these chemical gases are at risk of large-scale leakage during use and transportation, which will not only cause serious environmental problems such as ozone layer depletion and acid rain, but also cause serious damage to multiple organs of the human body. Therefore, it is necessary to develop efficient adsorbents to capture these toxic industrial gases and personal protection, reduce environmental pollution and optimize personal protection.
[0003] Currently, activated carbon is widely used as an adsorbent for filtering toxic gases in protective equipment. However, activated carbon has problems such as unclear pore structure, unadjustable composition, and weak interaction with toxic gases (such as sulfur dioxide and ammonia). These problems result in low adsorption capacity and poor selectivity under low concentration conditions, limiting its effectiveness in practical applications and the research and development of new adsorbents.
[0004] Metal-Organic Frameworks (MOFs) are a type of crystalline porous functional materials assembled by metal ions or metal cluster units and organic ligands through coordination bonds. They not only have high specific surface area and porosity, but also can achieve precise regulation at the atomic scale by changing the metal center, ligand length or ligand surface functionalization while keeping the topological structure unchanged, so that they show good adsorption performance in capturing toxic gases. However, MOFs have poor structural stability when adsorbing corrosive and toxic gases, which leads to the collapse of the MOF structure. For example, during the adsorption of sulfur dioxide and ammonia, partial chemical adsorption occurs, destroying the metal-ligand coordination bonds in MOFs, causing the MOFs skeleton to collapse. In addition, MOFs materials are also easily affected by the humidity in the environment, and the competitive adsorption of water vapor will also cause MOFs to reduce their adsorption capacity in a humid environment.
[0005] Therefore, while keeping the topology of the MOFs material unchanged, exploring the effects of different metal types in the MOFs structure on the adsorption cycle stability and adsorption performance of sulfur dioxide and ammonia, and designing and constructing a MOFs structure with high stability, high sulfur dioxide and ammonia capture performance, and the ability to overcome the negative effects of water vapor competitive adsorption are key factors in realizing the application of MOFs in capturing toxic gases. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of poor adsorption cycle stability, low adsorption capacity and water vapor competitive adsorption existing in the prior art for MOFs to adsorb sulfur dioxide and ammonia, and propose a preparation method of a series of M-TCBB metal organic framework materials and their application in adsorbing sulfur dioxide and ammonia. [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid (H4TCBB) is used as an organic ligand, and yttrium salt, zirconium salt, hafnium salt, cerium salt and thorium salt are used to prepare the series of M-TCBB metal organic framework materials by a solvothermal method. The series of M-TCBB metal organic framework materials prepared by the present invention are used for adsorbing sulfur dioxide and ammonia, have high stability and high capture performance, and show the characteristics of water vapor enhanced sulfur dioxide and ammonia adsorption.
[0007] The technical solution of the present invention is:
[0008] The present invention provides a method for preparing a series of M-TCBB metal organic framework materials, comprising the following steps:
[0009] [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid (H4TCBB) is used as an organic ligand, and it is dispersed in a solution with a metal salt according to a certain mass ratio, and a regulator is added, and a solvent thermal reaction is carried out at 100-120°C for a reaction time of 15min-72h; after the reaction is completed, centrifugation is performed, and the precipitate is taken, washed, and dried to obtain a series of M-TCBB metal organic framework materials;
[0010] Wherein, the metal salt includes any one or more of yttrium (Y) salt, zirconium (Zr) salt, hafnium (Hf) salt, cerium (Ce) salt, and thorium (Th) salt.
[0011] The series of M-TCBB metal organic framework materials prepared by the present invention include Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB, and Th-TCBB. The materials are constructed by selecting different metals (M: Y, Zr, Hf, Ce, Th) under the condition of maintaining the (4,8)-connected flu topology, and the adsorption stability and adsorption performance of sulfur dioxide and ammonia by different metal types in the M-TCBB structure are explored. First of all, from the structural point of view, the M-TCBB composed of different metal types has some differences in specific surface area and pore volume, as follows: the specific surface areas of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB are 1180, 1070, 980, 940 and 920 m 2 / g, and the corresponding pore volumes are 0.49, 0.45, 0.46, 0.38 and 0.36 cm 3 / g. Generally, differences in pore parameters will result in different adsorption capacities of adsorbent materials. Secondly, differences in the electronegativity of metal types will also result in different forces between the metal cluster center of the material and the adsorbed gas. In the present invention, Y, Zr, Hf, Ce and Th are selected as metals to construct a series of M-TCBB metal-organic framework materials, and the electronegativity of the metal types is expressed as Zr>Ce>Hf>Th>Y. For sulfur dioxide molecules, the stronger the electronegativity of the metal type, the stronger the affinity with the oxygen atoms in sulfur dioxide; similarly, the stronger the electronegativity of the strong metal type, the stronger the affinity with the nitrogen atoms in the ammonia molecules. Therefore, by selecting a specific metal type, the adsorption mechanism of the corresponding M-TCBB framework structure for sulfur dioxide and ammonia is directionally strengthened. Finally, for carboxylic acid ligands, compared with trivalent metal types, the coordination bond energy formed between the tetravalent metal type and the oxygen atom in the carboxylic acid ligand is higher, and its corresponding framework structure is more stable, which is beneficial to improve the material's adsorption cycle stability for sulfur dioxide and ammonia.
[0012] Further, the metal salt includes any one or more of yttrium nitrate, zirconium tetrachloride, hafnium tetrachloride, cerium ammonium nitrate, and thorium nitrate;
[0013] The solution is N,N-dimethylformamide or a mixture of N,N-dimethylformamide and water, and the regulator is any one or more of 2-fluorobenzoic acid, formic acid and acetic acid.
[0014] Furthermore, when yttrium nitrate is used as the metal salt, the mass ratio of yttrium nitrate to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.6-3); the solution is a mixture of N,N-dimethylformamide and water, which is composed of a mixture in a volume ratio of 1:(0.3-0.6), and 2-fluorobenzoic acid is added as a regulator; the mass ratio of yttrium nitrate to 2-fluorobenzoic acid is 1:(5-35); and Y-TCBB is finally prepared.
[0015] Furthermore, when zirconium tetrachloride is used as the metal salt, the mass ratio of zirconium tetrachloride to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.5-2); the solution is N,N-dimethylformamide, acetic acid is the regulator, and N,N-dimethylformamide and acetic acid are mixed in a volume ratio of 1:(0.3-0.8); and finally Zr-TCBB is prepared.
[0016] Furthermore, when hafnium tetrachloride is used as the metal salt, the mass ratio of hafnium tetrachloride to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.3-3); the solution is N,N-dimethylformamide, and acetic acid is the regulator; the volume ratio of N,N-dimethylformamide and acetic acid is 1:(0.3-0.8); and finally Hf-TCBB is prepared.
[0017] Furthermore, when ammonium cerium nitrate is used as the metal salt, the mass ratio of ammonium cerium nitrate to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.1-9); the solution is a mixture of N,N-dimethylformamide and water, and acetic acid is a regulator; the volume ratio of N,N-dimethylformamide, water and acetic acid is 1:(0.2-0.4):(0.3-0.8); and finally Ce-TCBB is prepared.
[0018] Furthermore, when thorium nitrate is used as the metal salt, the mass ratio of thorium nitrate to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.1-6); the solution is a mixture of N,N-dimethylformamide and water, and formic acid is a regulator; the volume ratio of N,N-dimethylformamide, water and formic acid is 1:(0.2-0.4):(0.1-0.3); and Th-TCBB is finally prepared.
[0019] Furthermore, the solvent thermal reaction temperature is 105-115° C., and the solvent thermal reaction time is 25 h to 45 h.
[0020] Furthermore, N,N-dimethylformamide and acetone are used as detergents to wash the precipitate 3 to 5 times; the drying temperature is 80 to 120° C., and the drying time is 6 to 12 hours.
[0021] The present invention also provides the use of a series of M-TCBB metal organic framework materials prepared by any of the preparation methods described above in the adsorption and capture of sulfur dioxide and ammonia in the air. In particular, the prepared series of M-TCBB are used as porous adsorbent materials to capture trace amounts of sulfur dioxide and ammonia in the air.
[0022] The present invention further provides the application of a series of M-TCBB metal organic framework materials prepared by any of the preparation methods described above to capture trace amounts of sulfur dioxide and ammonia under humid conditions. Under this application condition, water vapor promotes the adsorption of sulfur dioxide and ammonia. Zr-TCBB is selected as an adsorbent. Compared with dry conditions, under humid conditions, the adsorption amount of sulfur dioxide and ammonia captured is much higher than that captured under dry conditions, making it an adsorbent for capturing sulfur dioxide and ammonia under humid conditions.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention uses [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid (H4TCBB) as a ligand to construct a series of hexanuclear metal cluster-based MOFs (M-TCBB, M = Y, Zr, Hf, Ce, Th). A series of M-TCBBs are prepared by solvothermal reaction. The materials all have a (4,8)-connected flu topological structure. The effects of different metal types in the MOFs structure on the adsorption cycle stability and adsorption behavior of sulfur dioxide and ammonia are explored, thereby directionally enhancing the adsorption performance of sulfur dioxide and ammonia.
[0025] (2) The adsorbent with the series of M-TCBB metal-organic framework materials prepared by the present invention as the core can be used to capture sulfur dioxide and ammonia in the air. Among them, Zr-TCBB has high structural stability, and its adsorption amount remains unchanged after adsorbing sulfur dioxide, ammonia and water three times. At the same time, in the series of M-TCBB, Zr-TCBB also has a higher adsorption amount of sulfur dioxide and ammonia, indicating that Zr-TCBB can better balance the adsorption stability and adsorption amount of sulfur dioxide and ammonia. The adsorbent with Zr-TCBB prepared by the present invention as the core can effectively capture sulfur dioxide and ammonia under low concentration and humid conditions. In addition to high stability, Zr-TCBB shows humidity-enhanced characteristics in the capture of sulfur dioxide and ammonia under humid conditions, that is, the adsorption amount of sulfur dioxide and ammonia is enhanced under humid conditions.
[0026] (3) The series of M-TCBB metal organic framework materials prepared by the method of the present invention well explain the key influence mechanism of different metal types on the adsorption cycle stability and adsorption behavior of sulfur dioxide and ammonia, and promote the research and development of new and efficient MOFs for capturing toxic gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The crystal structure and scanning electron microscope (SEM) image of Y-TCBB prepared in Example 1;
[0028] Figure 2 The crystal structure diagram and scanning electron microscope (SEM) image of Th-TCBB prepared in Example 5;
[0029] Figure 3 Theoretical and experimental powder X-ray diffraction (PXRD) comparison spectra of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB prepared in Examples 1 to 5;
[0030] Figure 4The sulfur dioxide adsorption isotherms of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB prepared in Examples 1 to 5 at room temperature and the powder X-ray diffraction (PXRD) spectra after three adsorptions;
[0031] Figure 5 Ammonia adsorption isotherms at room temperature and powder X-ray diffraction (PXRD) spectra after three adsorptions of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB prepared in Examples 1 to 5;
[0032] Figure 6 The water adsorption isotherm of Zr-TCBB prepared in Example 2 at room temperature and the X-ray powder diffraction (PXRD) comparison spectrum after three water adsorptions;
[0033] Figure 7 These are the breakthrough curves of sulfur dioxide and ammonia in the fixed bed experiment under dry and wet conditions for the Zr-TCBB prepared in Example 2. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In order to further understand the present invention, the present invention will be further described in conjunction with the accompanying drawings and embodiments.
[0036] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0037] Example 1
[0038] 1.15 g of hydrated yttrium nitrate, 0.76 g of [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid and 7.5 g of 2-fluorobenzoic acid were ultrasonically dispersed in a mixed solution consisting of 150 mL of N,N-dimethylformamide and 60 mL of deionized water, and the mixture was subjected to solvent thermal reaction at 120°C for 72 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain a precipitate. The precipitate was washed with 300 mL of N,N-dimethylformamide and 400 mL of acetone for 3 to 5 times, respectively, and the washed precipitate was dried at 120°C for 10 h to obtain a yttrium-based metal organic framework material Y-TCBB.
[0039] Example 2
[0040] 0.932g zirconium tetrachloride and 0.508g [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid were ultrasonically dispersed in a mixed solution consisting of 200mL N,N-dimethylformamide and 100mL acetic acid, and the solvent thermal reaction was carried out at 120°C for 72h; after the reaction was completed, it was cooled to room temperature, centrifuged, and the precipitate was taken; the precipitate was washed with 300mL N,N-dimethylformamide and 400mL acetone respectively, and the washed precipitate was dried at 120°C for 10h to obtain a zirconium-based metal organic framework material Zr-TCBB.
[0041] Example 3
[0042] 1.28g of hafnium tetrachloride and 0.508g of [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid were ultrasonically dispersed in a mixed solution consisting of 200mL of N,N-dimethylformamide and 100mL of acetic acid, and the solvent thermal reaction was carried out at 120°C for 72h; after the reaction was completed, the mixture was cooled to room temperature, centrifuged, and the precipitate was taken; the precipitate was washed with 300mL of N,N-dimethylformamide and 400mL of acetone respectively, and the washed precipitate was dried at 120°C for 10h to obtain the hafnium-based metal organic framework material Hf-TCBB.
[0043] Example 4
[0044] 8.766g of ammonium cerium nitrate and 1.02g of [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid were ultrasonically dispersed in a mixed solution consisting of 100mL of N,N-dimethylformamide, 60mL of acetic acid and 30mL of deionized water, and placed on an aluminum heating plate at a speed of 500r / min and stirred at 100°C for 15min; after the reaction was completed, it was cooled to room temperature, centrifuged and the precipitate was taken; the precipitate was washed with 300mL of N,N-dimethylformamide and 400mL of acetone respectively, and the washed precipitate was dried at 100°C for 10h to obtain a cerium-based metal-organic framework material Ce-TCBB.
[0045] Example 5
[0046] 2 g of hydrated thorium nitrate and 0.356 g of [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid were ultrasonically dispersed in a mixed solution consisting of 80 mL of N,N-dimethylformamide, 17.5 mL of formic acid and 17 mL of deionized water, and subjected to solvent thermal reaction at 120°C for 24 h. After the reaction was completed, the mixture was cooled to room temperature, centrifuged and the precipitate was taken. The precipitate was washed with 300 mL of N,N-dimethylformamide and 400 mL of acetone respectively, and the washed precipitate was dried at 120°C for 10 h to obtain a thorium-based metal-organic framework material Th-TCBB.
[0047] Example 6
[0048] 0.932g zirconium tetrachloride and 1.0g [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid were ultrasonically dispersed in a mixed solution consisting of 200mL N,N-dimethylformamide and 100mL acetic acid, and the solvent thermal reaction was carried out at 110°C for 48h; after the reaction was completed, the mixture was cooled to room temperature, centrifuged, and the precipitate was taken; the precipitate was washed with 300mL N,N-dimethylformamide and 400mL acetone respectively, and the washed precipitate was dried at 100°C for 8h to obtain a zirconium-based metal organic framework material Zr-TCBB.
[0049] Example 7
[0050] 0.932g zirconium tetrachloride and 1.864g [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid were ultrasonically dispersed in a mixed solution consisting of 200mL N,N-dimethylformamide and 100mL acetic acid, and the solvent thermal reaction was carried out at 100°C for 60h; after the reaction was completed, the mixture was cooled to room temperature, centrifuged, and the precipitate was taken; the precipitate was washed with 300mL N,N-dimethylformamide and 400mL acetone respectively, and the washed precipitate was dried at 110°C for 12h to obtain a zirconium-based metal organic framework material Zr-TCBB.
[0051] Test Case
[0052] 1. Single crystal structure analysis and scanning electron microscope (SEM) imaging
[0053] The structures of the yttrium-based and thorium-based metal organic framework material single crystals prepared in Example 1 and Example 5 were analyzed using a smart Kappa single crystal diffractometer from Bruker, Germany, to obtain their crystallographic data. The results are shown in Table 1.
[0054] Table 1 Crystallographic data of metal organic framework materials prepared in Example 1 and Example 5
[0055]
[0056] Table 1 shows that Y-TCBB and Th-TCBB have the same unit cell parameters, both are tetragonal, and have I4 / mmm space group.
[0057] The yttrium-based and thorium-based metal organic framework materials prepared in Example 1 and Example 5 were imaged using a Hitachi SU8030 scanning electron microscope.
[0058] Figure 1 (left) and Figure 2 (Left) Crystal structures of Y-TCBB and Th-TCBB, Figure 1 (right) and Figure 2(Right) Scanning electron microscope images of Y-TCBB and Th-TCBB, respectively. It can be seen that the change of metal type does not affect the overall structure of the framework, and both materials present a regular octahedral shape with uniform crystal size distribution.
[0059] 2. X-ray powder diffraction (PXRD) analysis
[0060] The materials synthesized in Examples 1 to 5 were characterized by using a STOE-STADIP X-ray powder diffractometer. The double diffraction angle range was 2-20°. The test voltage and current were 40 kV and 40 mA, respectively. Cu-Kα rays were used with a wavelength of 0.15406 nm.
[0061] Figure 3 PXRD spectra of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB prepared in Examples 1 to 5. Figure 3 It can be seen that the PXRD spectra of the five metal organic framework materials synthesized in Examples 1 to 5 are the same, indicating that five materials with high purity are synthesized and have the same topological structure. However, due to the short synthesis time and small crystal size of Ce-TCBB, the diffraction of the PXRD figure is weak, but the PXRD spectrum confirms the consistency of the structure.
[0062] 3. Sulfur dioxide adsorption isotherm test
[0063] The five metal organic framework materials prepared in Examples 1 to 5 were subjected to sulfur dioxide adsorption isotherm tests using a Micromeritics 3Flex gas adsorption instrument.
[0064] like Figure 4 As shown, during the first sulfur dioxide adsorption process, the adsorption amounts of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB at 298K and 1 bar were 8.78, 10.98, 8.45, 8.59 and 5.31 mmol / g, respectively, and at 0.1 bar, the adsorption amounts of the above materials were 5.20, 6.38, 4.80, 5.03, 3.09 mmol / g, respectively. After three sulfur dioxide adsorptions, the overall adsorption amounts of Zr-TCBB, Hf-TCBB and Th-TCBB did not change significantly. Figure 4 The PXRD spectra confirmed the structural integrity of the three MOFs. However, the adsorption amounts of Y-TCBB and Ce-TCBB decreased to 4.57 and 5.38 mmol / g, respectively, and the characteristic peaks of Y-TCBB at 5.8° and 7.3° and Ce-TCBB at 5.6° and 7.1° became broader, indicating that the skeleton structure of the two materials partially collapsed during the cyclic adsorption process.
[0065] 4. Ammonia adsorption isotherm test
[0066] The ammonia adsorption isotherms of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB prepared in Examples 1 to 5 were tested using a Micromeritics 3Flex gas adsorption instrument. The results are as follows: Figure 5 As shown. During the first ammonia adsorption process, the five materials showed different adsorption behaviors. At 298K and 1bar, the adsorption amounts of Y-TCBB, Zr-TCBB, Hf-TCBB, Ce-TCBB and Th-TCBB were 12.53, 11.58, 9.98, 12.46 and 6.08mmol / g, respectively. At 0.1bar, the adsorption amounts of the above materials were 5.12, 3.53, 3.30, 4.27, 2.27mmol / g, respectively. After three ammonia adsorptions, the ammonia adsorption amounts of Zr-TCBB, Hf-TCBB and Th-TCBB remained stable. Figure 5 The PXRD spectra show that after three ammonia adsorptions, Zr-TCBB, Hf-TCBB and Th-TCBB can still maintain structural integrity. For Y-TCBB and Ce-TCBB, the adsorption amounts after three adsorptions are 6.54 and 7.63 mmol / g, respectively, which are still at a relatively high level. Combined with PXRD analysis, the characteristic peaks of Y-TCBB at 5.8° and 7.3° are significantly shifted, and the characteristic peaks of Ce-TCBB at 5.6° and 7.1° are significantly broadened, and the peak intensity is weakened, indicating that the skeleton structure of Y-TCBB and Ce-TCBB partially collapses. For Ce-TCBB, in the skeleton structure, Ce is a mixed valence state of Ce(III) and Ce(IV), and the valence state ratio of Ce(III) / Ce(IV) is 1:4; for Y-TCBB, the single low valence state characteristics of Y(III) result in its coordination bond energy being slightly lower than that of the tetravalent metal center. The above data show that for carboxylic acid ligands, the coordination bond energy formed between the tetravalent metal center and the oxygen atom in the carboxylic acid ligand is higher, and its corresponding skeleton structure is more stable, which is suitable for the adsorption of sulfur dioxide and ammonia.
[0067] 5. Water adsorption isotherm test
[0068] The water adsorption isotherm of Zr-TCBB prepared in Example 2 was tested using a Micromeritics 3Flex vapor adsorption instrument. Three cycles of water adsorption measurements confirmed the good water cycle stability of Zr-TCBB. At the same time, no obvious changes were found in the PXRD spectra of Zr-TCBB after three cycles of water adsorption, indicating that the structure of the material remained intact. The results are as follows: Figure 6 shown.
[0069] VI. Penetration test of sulfur dioxide and ammonia under dry and wet conditions
[0070] At 1000 mg / m 3 The sulfur dioxide penetration experiment of Zr-TCBB material under dry and 80% RH conditions was investigated. Figure 7 Middle left figure. Under dry and wet conditions, the adsorption amount of Zr-TCBB is 0.2 and 0.5 mmol / g, respectively. This shows that the adsorption amount of sulfur dioxide by Zr-TCBB in a high humidity environment is significantly higher than that under dry conditions. This experimental result shows that Zr-TCBB is more suitable for sulfur dioxide capture under wet conditions.
[0071] At 2000mg / m 3 The ammonia penetration test of Zr-TCBB material under dry and 80% RH conditions was investigated. Figure 7 Middle right picture. Under dry and wet conditions, the adsorption amount of Zr-TCBB reached 5.4mmol / g and 9.0mmol / g respectively. This shows that the ammonia adsorption amount of Zr-TCBB in high humidity environment is also higher than that in dry conditions, and it is more suitable for the capture of ammonia under wet conditions.
[0072] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, modification, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a series of M-TCBB metal organic framework materials, characterized in that: The following steps are involved: [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid (H4TCBB) is used as an organic ligand, which is dispersed in a solution with a metal salt according to a certain mass ratio, and a regulator is added to carry out a solvent thermal reaction at 100-120° C. The reaction time is 15 min-72 h. After the reaction is completed, centrifugation is performed, and the precipitate is taken, washed, and dried to obtain a series of M-TCBB metal organic framework materials; wherein the metal salt includes any one or more of yttrium salts, zirconium salts, hafnium salts, cerium salts, and thorium salts.
2. The preparation method according to claim 1, characterized in that: The metal salt includes any one or more of yttrium nitrate, zirconium tetrachloride, hafnium tetrachloride, cerium ammonium nitrate, and thorium nitrate; The solution is N,N-dimethylformamide or a mixture of N,N-dimethylformamide and water, and the regulator is any one or more of 2-fluorobenzoic acid, formic acid and acetic acid.
3. The preparation method according to claim 2, characterized in that: When yttrium nitrate is used as the metal salt, the mass ratio of yttrium nitrate to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.6-3); the solution is a mixed solvent of N,N-dimethylformamide and water, and 2-fluorobenzoic acid is added as a regulator; the N,N-dimethylformamide and the aqueous solution are mixed in a volume ratio of 1:(0.3-0.6), and the mass ratio of yttrium nitrate to 2-fluorobenzoic acid is 1:(5-35); Y-TCBB was prepared.
4. The preparation method according to claim 2, characterized in that: When zirconium tetrachloride is used as the metal salt, the mass ratio of zirconium tetrachloride to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.5-2); the solution is N,N-dimethylformamide, and acetic acid is the regulator; the volume ratio of N,N-dimethylformamide to acetic acid is 1:(0.3-0.8); Zr-TCBB was prepared.
5. The preparation method according to claim 2, characterized in that: When hafnium tetrachloride is used as the metal salt, the mass ratio of hafnium tetrachloride to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.3-3); the solution is N,N-dimethylformamide, and acetic acid is the regulator; the volume ratio of N,N-dimethylformamide to acetic acid is 1:(0.3-0.8); Hf-TCBB was prepared.
6. The preparation method according to claim 2, characterized in that: When ammonium cerium nitrate is used as the metal salt, the mass ratio of ammonium cerium nitrate to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.1-9); the solution is a mixture of N,N-dimethylformamide and water, and acetic acid is a regulator; the volume ratio of N,N-dimethylformamide, water and acetic acid is 1:(0.2-0.4):(0.3-0.8); Ce-TCBB was prepared.
7. The preparation method according to claim 2, characterized in that: When thorium nitrate is used as the metal salt, the mass ratio of thorium nitrate to [9,9'-bicarbazole]-3,3',6,6'-tetracarboxylic acid is 1:(0.1-6); the solution is a mixture of N,N-dimethylformamide and water, and formic acid is a regulator; the volume ratio of N,N-dimethylformamide, water and formic acid is 1:(0.2-0.4):(0.1-0.3); Th-TCBB was prepared.
8. The preparation method according to claim 1, characterized in that: The precipitate is washed 3 to 5 times using N,N-dimethylformamide and acetone as detergents; the drying temperature is 80 to 120° C., and the drying time is 6 to 12 hours.
9. Application of a series of M-TCBB metal organic framework materials prepared by the preparation method according to any one of claims 1 to 8 in the adsorption and capture of sulfur dioxide and ammonia in the air.
10. Use of a series of M-TCBB metal organic framework materials prepared by the preparation method according to any one of claims 1 to 8 in adsorbing or capturing sulfur dioxide and ammonia in humid air.
Citation Information
Patent Citations
Hydrophobic mixed-valence metal organic framework material, preparation method thereof and method for preparing hydrogen peroxide through photocatalysis
CN117551275A
Composite material and preparation method thereof, photoelectric device and display device
CN117651436A
Hexahydro pyrimidopyrimidine compound and organic thin film and organic semiconductor device using the same
JP2024024318A
Cited By
Air purification material for removing alkaline pollutants in air as well as preparation method and application of air purification material
CN120754831A
Air purification material for removing alkaline contaminants in air and preparation method and application thereof
CN120754831B
Air purification material for removing acidic pollutants in air as well as preparation method and application of air purification material
CN120861017A
Air purification material for removing acidic pollutants in air and preparation method and application thereof
CN120861017B